The complexities and challenges of be(com)ing a teacher and a teacher educator - Flores, Maria Assunção (2017)
Much has been written about the process of be(com)ing a teacher. Issues such as the professional socialisation of new teachers, the need for support and guidance, mentoring and induction, the formation of teacher identity and opportunities to learn in the workplace have been addressed. Existing literature points to the complex and ongoing nature of the process of becoming a teacher, which relates not only to issues pertaining to the content and form of teacher education programmes, but also to motivational, contextual and professional aspects (Flores 2006; Feiman- Nemser 2012). Less is known, however, about the process of be(com)ing a teacher-educator, particularly as far as his/her education and opportunities for continuing professional development (CPD) are concerned, as well as his/her professional identities, despite the growing interest in the topic in recent years (Vanassche and Kelchtermans 2014; Izadinia 2014; Lunenberg, Dengerink, and Korthagen 2014).